2009
DOI: 10.1208/s12249-009-9326-y
|View full text |Cite
|
Sign up to set email alerts
|

Cogrinding as a Tool to Produce Sustained Release Behavior for Theophylline Particles Containing Magnesium Stearate

Abstract: Abstract. The aim of the present study was to explore the cogrinding technique as a tool to slow down the drug release from capsule formulations. To this end, the physical mixtures of theophyllinemagnesium stearate were prepared and subjected to different milling times (1, 15, 30, 120 min). In order to investigate the effect of magnesium stearate concentration on drug release, various concentrations of magnesium stearate (1%, 3%, 5%, and 10%, w/w) were used. The dissolution rate of the drug from coground sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
3
11
1
Order By: Relevance
“…This contradicts previous reports, that co-grinding drug powders with the hydrophobic MgSt retards the dissolution of the drug in powder mixtures by preventing wetting and water penetration (Javadzadeh et al, 2012;Nokhodchi et al, 2009). In this study, we believe the increased dissolution rate from the MgSt-mechanofused powder is due to the enhanced powder de-agglomeration.…”
Section: In Vitro Dissolution Studiescontrasting
confidence: 93%
See 1 more Smart Citation
“…This contradicts previous reports, that co-grinding drug powders with the hydrophobic MgSt retards the dissolution of the drug in powder mixtures by preventing wetting and water penetration (Javadzadeh et al, 2012;Nokhodchi et al, 2009). In this study, we believe the increased dissolution rate from the MgSt-mechanofused powder is due to the enhanced powder de-agglomeration.…”
Section: In Vitro Dissolution Studiescontrasting
confidence: 93%
“…However, there is an extensive historical concern that the hydrophobic properties of some dry coating agents such as magnesium stearate will retard drug dissolution in the powder mixture when over-blended or co-ground (Javadzadeh et al, 2012;Nokhodchi et al, 2009) . Over blending of magnesium stearate is also known to have a negative effect on tableting behaviour (Shah and Mlodozeniec, 1977;Strickland Jr et al, 1956;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mg stearate has Mg +2 as a cationic root, so it can interfere with the agglomeration process. 55,56 Stearic acid exists in a solid state at room temperature, which is thought to help in the formation of a thin layer surrounding the drug nanodispersion. 57 The amphiphilic nature of stearic acid makes it perform as a boundary between theophylline nanoparticles and the hydrophilic medium in the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…From Table I it could be concluded that the release profile of nanoparticles prepared with high MW chitosan is similar to that of nanoparticles prepared with medium MW chitosan, but different with that of nanoparticles prepared with low MW chitosan. Dissolution efficiency (DE) was calculated from the area under the dissolution curve at time and expressed as percentage of the area of the rectangle described by 100% dissolution in the same time (24)(25)(26)(27). Insulin nanoparticles prepared with chitosan of high MW showed higher dissolution efficiency (Table I).…”
Section: Resultsmentioning
confidence: 99%